Private Life in the Public Storytelling. Sicilian Letters from the First World War - Riccio, Elena (Populismo y propaganda: entre el presente y el pasado, 2020)
The present study deals with the public use of private writings during the First World War through the analysis of some epistolary testimonies dating back to a period ranging from 1915 to 1917. Written by Sicilian soldiers, the letters were published in Italy one hundred years later in a critical edition.